2015
DOI: 10.1016/j.tetlet.2014.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Computational studies of electronic circular dichroism spectra predict absolute configuration assignments for the guanine oxidation product 5-carboxamido-5-formamido-2-iminohydantoin

Abstract: Oxidation of the guanine heterocycle by two electrons can yield the chiral product 5-carboxamido-5-formamido-2-iminohydantoin (2Ih). The 2Ih free base enantiomers were synthesized from 2′-deoxyguanosine oxidized with a Cu(II)/H2O2 oxidant system followed by hydrolysis of the N-glycosidic bond. These isomers were each studied by electronic circular dichroism spectroscopy for determination of their absolute configurations. Time-dependent density functional theory calculations of the expected spectra were complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 34 publications
2
22
0
Order By: Relevance
“…Use of a Hypercarb column allowed separation of the d2Ih and dSp diastereomers for which the absolute configurations and elution order on this HPLC column are known. 42 , 62 In the current studies, the R and S isomers of d2Ih were observed in a 1:2 ratio, respectively, for both oxidation reactions studied, while the R and S isomers of dSp were observed in a 1:1 ratio. Furthermore, these ratios did not change under any of the reaction conditions studied.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Use of a Hypercarb column allowed separation of the d2Ih and dSp diastereomers for which the absolute configurations and elution order on this HPLC column are known. 42 , 62 In the current studies, the R and S isomers of d2Ih were observed in a 1:2 ratio, respectively, for both oxidation reactions studied, while the R and S isomers of dSp were observed in a 1:1 ratio. Furthermore, these ratios did not change under any of the reaction conditions studied.…”
Section: Resultssupporting
confidence: 50%
“… 43 However, our previous time-dependent density functional theory studies on the UV–vis and ECD properties for dSp and d2Ih allow us to use these previous results to determine the relative difference in extinction coefficient between these two compounds at the wavelength monitored. 42 , 43 These calculations determined the ε 240 nm for d2Ih to be ∼30% less than that of dSp ; therefore, the ε 240 nm value used to quantify d2Ih was calculated to be 2290 L·mol –1 ·cm –1 . 45 The Fenton reaction was initially conducted with the Fe(II)/EDTA catalyst and 10 mM H 2 O 2 under aerobic conditions to give 5% conversion to product.…”
Section: Resultsmentioning
confidence: 99%
“… 58 The dSp diastereomers were individually purified while the diastereomers of dGh were studied as a mixture because they readily interconvert. 59 Syntheses of dZ and the ( R )- and ( S )-d2Ih 60 diastereomers were achieved in a 15-mer DNA oligomer containing a single dG site (5′-AAT CCA CGA CAC CTC-3′) following literature methods. 17 , 24 All product oligomers were purified using an analytical ion-exchange HPLC column that resolves diastereomeric products ( Figure S1 ).…”
Section: Methodsmentioning
confidence: 99%
“…22,60 Briefly, 10 μM ODN in 20 mM NaP i buffer (pH 7.4) and 100 mM NaCl was incubated with 5 μM NiCR at 37 °C for 20 min prior to the addition of 100 μM KHSO 5 , and the reaction was allowed to progress for 30 min. The reaction was quenched by adding 50 mM HEPES (pH 8).…”
Section: Methodsmentioning
confidence: 99%
“…The absoluteconfigurations for the diastereomers of 2Ih and Sp have previously been determined, as well as their elution order in an ODN on the ion-exchange HPLC column used in the present studies. 60,61 These ODNs were further purified by HPLC to obtain > 95% purity before use. The ODNs with 2Ih or Sp were characterized by either ESI-MS for ODNs 1 (G: calcd 5357.5, found 5356.9; ( S )-2Ih or ( R )-2Ih): calcd 5391.5, found 5391.0 and 5391.1, respectively; a mixture of the Sp diastereomers: calcd 5389.5, found 5389.6) or MALDI-MS for ODNs 3 (G: calcd 4463.8, found 4464.2; mixture of 2Ih diastereomers: calcd 4497.8, found 4498.2; mixture of Sp diastereomers: calcd 4495.8, found 4496.6).…”
Section: Methodsmentioning
confidence: 99%